2023
DOI: 10.1038/s41419-023-05975-x
|View full text |Cite
|
Sign up to set email alerts
|

GOLPH3 promotes endotoxemia-induced liver and kidney injury through Golgi stress-mediated apoptosis and inflammatory response

Abstract: Sepsis is a serious clinical condition characterized by a systemic inflammatory response, a leading cause of acute liver and kidney injury, and is associated with a high morbidity and mortality. Understanding the molecular mechanisms underlying the acute liver and kidney injury is crucial for developing an effective therapy. Golgi apparatus plays important roles and has various substrates mediating cellular stress responses. Golgi phosphoprotein 3 (GOLPH3), linking Golgi membranes to the cytoskeleton, has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Because the lung, liver, and kidney are vital organs susceptible to LPS toxicity in mice [27], we further examined whether the intraperitoneal administration of galgravin attenuates LPS-induced histological changes in these organs of LPS-challenged mice. We found that galgravin improved hilum congestion, reduced alveolar septal thickening, and significantly diminished alveolar hemorrhage in the lung tissues of LPS-challenged mice (Figure 5A-C,G).…”
Section: Galgravin Attenuates Inflammatory Responses In Multiple Orga...mentioning
confidence: 99%
“…Because the lung, liver, and kidney are vital organs susceptible to LPS toxicity in mice [27], we further examined whether the intraperitoneal administration of galgravin attenuates LPS-induced histological changes in these organs of LPS-challenged mice. We found that galgravin improved hilum congestion, reduced alveolar septal thickening, and significantly diminished alveolar hemorrhage in the lung tissues of LPS-challenged mice (Figure 5A-C,G).…”
Section: Galgravin Attenuates Inflammatory Responses In Multiple Orga...mentioning
confidence: 99%
“… 6 , 7 Changes in gene and protein expression and functional abnormalities are common events during the sepsis-mediated progression of ALI. 8 , 9 In spite of the rapid research advances, the pathophysiology of sepsis-induced ALI and the interventions to cure ALI are still limited. Hence, it is imperative to comprehensively investigate the underlying mechanisms of sepsis-induced acute liver injury (SALI) and explore the potential therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%